Gamma-Secretase Inhibitors Attenuate Neurotrauma and Neurogenic Acute Lung Injury in Rats by Rescuing the Accumulation of Hypertrophic Microglia - Hung-Jung Lin; Chien-Chin Hsu; Chung-Ching Chio; Yu-Feng Tian; Mao-Tsun Lin; Ting-Wei Lin; Chih-Hsien Chang; Ching-Ping Chang (Cellular Physiology and Biochemistry, 2017)
Background/Aims: In response to traumatic brain injury (TBI), activated microglia exhibit changes in their morphology from the resting ramified phenotype toward the activated hypertrophic or amoeboid phenotype. Here, we provide the first description of the mechanism underlying the neuroprotective effects of γ-secretase inhibitors on TBI outcomes in rats. Methods: The neuroprotective effects of γ-secretase inhibitors such as LY411575 or CHF5074 on TBI-induced neurotoxicity were analysed using a neurological motor function evaluation, cerebral contusion assay, immunohistochemical staining for microglia phenotypes, lung injury score and Evans Blue dye extravasation assay of brain and lung oedema. Results: Hypertrophic or amoeboid microglia accumulated in the injured cortex, the blood-brain-barrier was disrupted and neurological deficits and acute lung injury were observed 4 days after TBI in adult rats. However, a subcutaneous injection of LY411575 (5 mg/kg) or CHF5074 (30 mg/kg) immediately after TBI and once daily for 3 consecutive days post-TBI significantly attenutaed the accumulation of hypertrophic microglia in the injured brain, neurological injury, and neurogenic acute lung injury. Conclusion: Gamma-secretase inhibitors attenuated neurotrauma and neurogenic acute lung injury in rats by reducing the accumulation of hypertrophic microglia in the vicinity of the lesion.